Analisis Pengaruh Lokasi Dinding Geser Terhadap Pergeseran Lateral Bangunan Bertingkat Beton Bertulang 5 Lantai - Wibowo, Leonardus Setia Budi; Zebua, Dermawan (Universitas Dr. Soetomo, 2021)
Indonesia is one of the countries in the earthquake region. Therefore, it is necessary to build earthquake-resistant buildings to reduce the risk of material and life losses. Reinforced Concrete (RC) shear walls is one of effective structure element to resist earthquake forces. Applying RC shear wall can effectively reduce the displacement and story-drift of the structure. This research aims to study the effect of shear wall location in symmetric medium-rise building due to seismic loading. The symmetric medium rise-building is analyzed for earthquake force by considering two types of structural system. i.e. Frame system and Dual system. First model is open frame structural system and other three models are dual type structural system. The frame with shear walls at core and centrally placed at exterior frames showed significant reduction more than 80% lateral displacement at the top of structure.